Easytary / Afza Sariff ... [et al.] - Sariff, Afza; Razilan, Auni Batrisyia; Noorhisham, Batrisyia; Ahmad Tarmize, Mizan Maizatul Mayang Puteri; Azmi, Nur Aida Shahirah; Ab Rahman, Nur Zulaikha (2021)
Easytary is a name of our vending machine business that specializes in providing for the needs and it is also in the interest of women. It is not just like the usual vending machines such as selling water and food but we sell women’s necessities. As we can see in Malaysia, services like this may already exist but we often know about them. It is because, these services are mostly done abroad. For instance, wet tissues, sanitary towels and disposable panties. It may sound weird and funny, but in the unconscious service like this is very important and useful. We chose to sell it self-service by using vending machine because it is more innovative, does not require employees to maintain it and the most importantly is it can provide comfort to customers who want to buy. We chose to sell it self-service as the country’s economy has now collapsed due to the Covid-19 virus. So, the services that we provide are not very impactful as we do not have to use manpower as well as do not need to pay their wages. In addition, we have a well-planned strategy where we will place this vending machine in a place that has many people who need it such as in schools, offices and shopping malls. All these places has been our observation because, many women suffer from leakage problems. Due to this happening, then they will need sanitary pad at an immediate rate. In order to maintain the best quality to be provided to the customers, we have selected some well-known companies to collaborate together.